2011
DOI: 10.4049/jimmunol.1100216
|View full text |Cite
|
Sign up to set email alerts
|

Misfolded Truncated Protein τ Induces Innate Immune Response via MAPK Pathway

Abstract: Neuroinflammation plays a key role in the pathogenesis of Alzheimer’s disease and related tauopathies. We have previously shown that expression of nonmutated human truncated τ (151-391, 4R), derived from sporadic Alzheimer's disease, induced neurofibrillary degeneration accompanied by microglial and astroglial activation in the brain of transgenic rats. The aim of the current study was to determine the molecular mechanism underlying innate immune response induced by misfolded truncated τ. We found that purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 84 publications
2
38
0
Order By: Relevance
“…These pathways are involved in the production of pro-inflammatory cytokines (Buhrmann et al, 2011;Kovac et al, 2011;Sun et al, 2011) and have previously been shown to be induced by GS extract stimulation in PBMC (Toth et al, 2010). In addition, these pathways are also involved in other biological activities of GS such as decreasing ischemic reperfusion injury , killing of tumors (Ming et al, 2011;Wong et al, 2010) and reducing damage from oxidative stress .…”
Section: Discussionmentioning
confidence: 96%
“…These pathways are involved in the production of pro-inflammatory cytokines (Buhrmann et al, 2011;Kovac et al, 2011;Sun et al, 2011) and have previously been shown to be induced by GS extract stimulation in PBMC (Toth et al, 2010). In addition, these pathways are also involved in other biological activities of GS such as decreasing ischemic reperfusion injury , killing of tumors (Ming et al, 2011;Wong et al, 2010) and reducing damage from oxidative stress .…”
Section: Discussionmentioning
confidence: 96%
“…Exposure of extracellular misfolded truncated tau activates microglia through the MAPK pathway and induces the production of pro-inflammatory cytokines, including Interleukin-1β, Interleukin-6 and tumour necrosis factor alpha [263], which promote tau phosphorylation inside neurons [543]. Moreover, activated microglia may directly mediate tau propagation.…”
Section: Tau-mediated Neurodegenerationmentioning
confidence: 99%
“…Several previous studies have demonstrated that extracellular tau proteins play an important role in AD neuroinflammation [2830]. It was shown that the oligomeric tau that represents an early stage of tangle formation can be released into the extracellular space, where it behaves as a transmissible agent, spreading tau pathology throughout the brain in a ‘prion-like fashion’ [3133].…”
Section: Introductionmentioning
confidence: 99%